(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In modern construction practice, the rational use of raw materials and the reduction of environmental pollution are among the most urgent issues. Various industrial enterprises generate large amounts of secondary products that are typically classified as industrial waste. However, many of these by-products possess physical and chemical properties suitable for use in the production of construction materials. Considering that approximately 55% of construction materials are currently produced from natural raw materials, the introduction of industrial waste into the production of concrete fillers is of great scientific and practical importance. The use of such waste materials not only reduces the consumption of natural resources but also minimizes environmental pollution and contributes to sustainable development in the construction sector.